2010
DOI: 10.1509/jmkr.47.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Consumer Preferences for Complex Products: A Compositional Approach BasedonPaired Comparisons

Abstract: Conjoint analysis has become a widely accepted tool for preference measurement in marketing research, though its applicability and performance strongly depend on the complexity of the product or service. Therefore, self-explicated approaches are still frequently used because of their simple design, which facilitates preference elicitation when large numbers of attributes need to be considered. However, the direct measurement of preferences, or rather utilities, has been criticized as being imprecise in many ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 47 publications
0
56
0
4
Order By: Relevance
“…A more fine-grained assessment of consumers' preferences relies on a graded paired comparison (GPC, also referred to as constant sum paired comparison; see Day 1965;Netzer and Srinivasan 2011;Netzer, Toubia, Bradlow, Dahan, Evgeniou, Feinberg, Feit, Hui, Johnson, Liechty, Orlin and Rao 2008;Oishi, Hahn, Schimmack, Radhakrishan, Dzokoto and Ahadi 2005;Scholz, Meissner and Decker, 2010). In a GPC, individual consumers are instructed to rate the direction and intensity of their preference by dividing a particular sum of points among the two alternatives in every pair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more fine-grained assessment of consumers' preferences relies on a graded paired comparison (GPC, also referred to as constant sum paired comparison; see Day 1965;Netzer and Srinivasan 2011;Netzer, Toubia, Bradlow, Dahan, Evgeniou, Feinberg, Feit, Hui, Johnson, Liechty, Orlin and Rao 2008;Oishi, Hahn, Schimmack, Radhakrishan, Dzokoto and Ahadi 2005;Scholz, Meissner and Decker, 2010). In a GPC, individual consumers are instructed to rate the direction and intensity of their preference by dividing a particular sum of points among the two alternatives in every pair.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when individuals do not prefer one choice alternative over the other in a given pair, and are forced to assign a larger number to (at best, an arbitrarily chosen) choice alternative, GPC data are likely to suffer from logically 1 To date, no consensus exists as to what the optimal number of scale points is (Janhunen in press;Moors 2008). Some studies have suggested the optimal number of scale points to be seven: see Hofmans et al 2007;Lozano et al 2008;Weng 2004; few other studies suggested the optimal number of scale points to be higher than seven (see Alwin 1997;Scholz et al 2010), whereas other studies have argued that using five scale points is just as good as using seven or more scale points (see Böcker 1988;Churchill and Peter 1984). preference structures are not always logically consistent, and -even if an individual has a coherent preference structure -he/she may still provide preference data which are not completely in line with his/her preference structures.…”
Section: Introductionmentioning
confidence: 99%
“…The overall complexity of the digital camera category (with 30+ attribute levels) is parallel to product categories studied in prior research that elicits consumers' preferences for complex products (e.g., Park et al 2008;Netzer and Srinivasan 2011;Scholz et al 2010). The computer tablet category (with 70+ attribute levels) is considerably more complex than the ones used in extant methods, particularly in the context of decompositional preference elicitation methods.…”
Section: Empirical Investigationmentioning
confidence: 99%
“…Similar to prior studies in the literature (e.g., Scholz, et al 2010;Netzer and Srinivasan 2011), participants in all conditions first complete the preference measurement task, followed by an external validation task and a post-survey feedback task. Identical across the six experimental conditions, the external validation task comprises two choice questions, each including two camera profiles.…”
Section: Digital Cameramentioning
confidence: 99%
See 1 more Smart Citation